2006
DOI: 10.1111/j.1365-2966.2006.10834.x
|View full text |Cite
|
Sign up to set email alerts
|

First science with the Southern African Large Telescope: peering at the accreting polar caps of the eclipsing polar SDSS J015543.40+002807.2

Abstract: We describe briefly the properties of the recently completed Southern African Large Telescope (SALT), along with its first light imager SALTICAM. Using this instrument, we present 4.3 h of high‐speed unfiltered photometric observations of the eclipsing polar SDSS J015543.40+002807.2 with time‐resolution as short as 112 ms, the highest‐quality observations of this kind of any polar to date. The system was observed during its high‐luminosity state. Two accreting poles are clearly seen in the eclipse light curve.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(49 citation statements)
references
References 27 publications
(40 reference statements)
0
49
0
Order By: Relevance
“…The observations were performed with the Robert Stobie Spectrograph (RSS; Kobulnicky et al 2003) at the SALT O'Donoghue et al 2006). The long-slit spectroscopy mode of the RSS was used with a 1.25 arcsec slit width for most observations.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The observations were performed with the Robert Stobie Spectrograph (RSS; Kobulnicky et al 2003) at the SALT O'Donoghue et al 2006). The long-slit spectroscopy mode of the RSS was used with a 1.25 arcsec slit width for most observations.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The discovery paper of the first pulsating subdwarf O star (see above) contains the first published spectrum from SALT (Woudt et al, 2007). Several other modes of operation have been demonstrated (Romero-Colmenero et al, 2006). The flexible operation advantage has been made use of in producing the first very high time resolution photometry of rapid oscillations in an outbursting dwarf nova (Woudt & Warner, unpubl.…”
Section: The Southern African Large Telescope (Figure 2)mentioning
confidence: 97%
“…Also, the ability to concentrate on "time domain" astrophysics gives a specialized niche advantage. The first research paper to emerge from the new telescope immediately demonstrated the latter-light curves of an eclipsing 'polar ' at unprecedented time resolution, showing eclipse details of small luminous accreting regions on a white dwarf star (O'Donoghue et al, 2006; Figure 3). The discovery paper of the first pulsating subdwarf O star (see above) contains the first published spectrum from SALT (Woudt et al, 2007).…”
Section: The Southern African Large Telescope (Figure 2)mentioning
confidence: 98%
“…The primary mirror, which consists of 91 segments, is at a fixed elevation of 53 • . The telescope hosts four instruments, namely: SALTICAM, a science imaging camera operating between 3200-9000 Å [6], the RSS (Robert Stobie Spectrograph) a low-to medium resolution spectrograph [7], the BVIT (Berkeley Visible Image Tube) a high-time resolution photometer [8], and the HRS (High Resolution Spectrograph). The most recent instrument, the HRS, started science observations in 2014.…”
Section: South African Astronomical Observatorymentioning
confidence: 99%